Renewable and non-renewable energy consumption and economic growth in the US: A Markov-Switching VAR analysis. Issue 3 (May 2021) - Cevik, Emrah Ismail; Yıldırım, Durmuş Çağrı; Dibooglu, Sel
We examine the relationship between renewable and non-renewable energy consumption and economic growth in the United States. While the regime-dependent Granger causality test results for the non-renewable energy consumption and economic growth suggest bi-directional causality in both regimes, we cannot validate any causality between renewable energy consumption and economic growth. The US meets its energy demand from non-renewable sources; as such, renewable energy consumption does not seem to affect economic growth. Given the efficiency and productivity of renewable energy investments, we conclude that it is worthwhile to consider renewable energy inputs to replace fossil fuels given potential benefits in terms of global warming and climate change concerns. In this regard, increasing the R&D investments in the renewable energy sectors, increases in productivity and profitability of renewable energy investments are likely to accrue benefits in the long run.